Indirect Vector-Controlled Brushless Doubly-Fed Twin-Stator Induction Generator for Wind Energy Conversion Application - Mona I. Abdelkader; Ahmed K. Abdelsalam; Ahmed A. Hossameldin (Energies, 2020)
Wind energy conversion systems (WECSs) seem certain to play a major part in the world’s energy future due to their known high power capacity. The maximum power tracking is unavoidable due to the wind velocity variation and the non-linear relation with the turbine mechanical power. Commercial wind turbines are commonly coupled to either doubly-fed induction generators (DFIGs), wound rotor synchronous generators (WRSG) or permanent magnet synchronous generators (PMSGs). The DFIG-based WECS has several advantages over others. One of which is the power converter in such systems only deals with rotor power, hence the converter rating can run at reduced power rating. However, DFIG has the famous disadvantage of the presence of slip rings which leads to increased maintenance costs and outage times. Hence, brushless doublyfed induction machines (BDFIMs) can be considered as a viable alternative at the penalty of complicated controller requirement and limited decoupling control capability due to the machine’s non-linearity. In this paper, an enhanced performance indirect vector controller is proposed for WECS based on brushless doubly-fed twin-stator induction generator (BDFTSIG). The presented controller offers (i) simplified implementation, (ii) decoupled active-reactive power control, and (iii) a wide range of operation. The proposed controller performance is investigated under various loading conditions showing enhanced transient and minimal steady-state oscillations in addition to complete active/reactive power decoupling. The rigorous simulation and experimental results verify the claimed controller effectiveness under all possible operating conditions for sub- and super-synchronous speed range.